Synthesis and activity of proteasome inhibitors. (February 2014) - Dunn, Derek; Iqbal, Mohamed; Chatterjee, Sankar
Abstract Among its various catalytic activities, "chymotrypsin-like" activity of proteasome, a large multicatalytic proteinase complex has emerged as the focus of drug discovery efforts in cancer therapy. Herein, we report results from our investigation on a series of peptidomimetic inhibitors.